THE GENERIC NAMES PROPOSED FOR HYMENOMYCETES-VI*Brachybasidiaceae, Cryptobasidiaceae, Exobasidiaceae - M. A. DONK (Reinwardtia, 1956)
1. In this continuation of the author's nomenclatorial enumeration not only the three families mentioned in the subtitle are taken into consideration: about ten generic names of fungi which at one time or another have been attributed to the Exobasidiaceae and which are now excluded from the Hymenomycetes, are also dealt with. 2. The name' Cryptobasidiaceae is validly published.